Concentrated second‐harmonic generation from a single Al‐covered ZnS nanobelt. Issue 1 (13th December 2016) - Hu, Hongbo; Wang, Kai; Long, Hua; Han, Xiaobo; Chen, Jiawei; Wang, Bing; Lu, Peixiang
Abstract : Enhancing the SHG radiated from nanostructures is a crucial step toward its practical applications. Al allows for plasmon resonances that extend from the visible to the ultraviolet region. It not only confines the near‐infrared optical field, but also has high reflectance in the ultraviolet region, resulting in large SHG enhancements up to 60‐fold. The Al‐based hybrid nanostructures open up new possibilities for low‐cost, highly efficient nanolight sources at short wavelengths. Abstract: Here we report on the hybrid nanostructures where a single ZnS nanobelt was half‐covered with an aluminum (Al) film, which is an ideal platform for studying the second‐harmonic generation (SHG) enhancement effects of the Al coating. It was fabricated by the lift‐off process and allowed for the accurate comparison of the SHG intensity between the Al‐covered and the same bare ZnS nanobelt under consistent test conditions. The results indicate that the Al coating in the hybrid nanostructures not only confines the pumping laser in the ZnS effectively, but also concentrates the emitted SHG signal greatly, increasing the signal collection efficiency. By the combination of these two effects, ∼60 times enhancement of the SHG intensity is achieved at the optimized geometry size (width and thickness) of the ZnS nanobelts. The Al‐based hybrid nanostructures open up new possibilities for low‐cost, highly efficient and directional coherent nanolight sources at short wavelengths.